Development and utility of SSR markers based on Brassica sp. whole-genome in triangle of U - Sun, Nairan; Chen, Jisuan; Wang, Yuqi; Hussain, Iqbal; Lei, Na; Ma, Xinyan; Li, Weiqiang; Liu, Kaiwen; Yu, Hongrui; Zhao, Kun; Zhao, Tong; Zhang, Yi; et al. (Frontiers in Plant Science, 2024)
Simple sequence repeats (SSR), also known as microsatellites, are crucial molecular markers in both animals and plants. Despite extensive previous research on SSRs, the development of microsatellite markers in Brassica crops remains limited and inefficient. In this study, we conducted genome-wide microsatellite identification and marker development based on three recently sequenced basic species of Brassica crops in the triangle of U (Brassica rapa, B. nigra and B. oleracea), as well as three allotetraploids (B. juncea, B. napus and B. carinata) using public databases. A total of 79341, 92089, 125443, 173964, 173604, and 222160 SSR loci have been identified from the whole genome sequences of Brassica crops within the triangle of U crops, B. rapa (AA), B. nigra (BB), B. oleracea (CC), B. napus (AACC), B. juncea (AABB) and B. carinata (BBCC), respectively. Comparing the number distribution of the three allotetraploid SSR loci in the three subgenomes AA, BB and CC, results indicate that the allotetraploid species have significant reduction in the number of SSR loci in the genome compared with their basic diploid counterparts. Subsequently, the primers and the characteristics of microsatellites for most of them were accordingly designed on each chromosome of each of the six Brassica species, and their physical locations were identified. Moreover, we compared the basic species with their corresponding varieties, and found that the microsatellite characters between the allotetraploids and their corresponding basic species were very similar or almost identical. This suggests that the pattern of microsatellite distribution may be highly conserved during the differentiation of basic Brassica species and their allotetraploid counterparts. In addition, each of the 40 SSR primers was employed to investigate the polymorphism potential of B. rapa (85.27%), B. nigra (81.33%) and B. oleracea (73.45%), and B. rapa was found to have a higher cross-transfer rate among the basic species in the triangle of U. Meanwhile, a B-genome specific SSR marker, BniSSR23228 possessing the (AAGGA)3 sequence characteristics was obtained, and it was located in chromosome B3 with a total length of 97 bp. This study provides a basis for future genomics and genetic research on the relatedness of Brassica species.